A pharmacokinetic study to examine nicotine delivery from e cigarettes and a conventional cigarette in healthy subjects during a brief period of ad libitum use - Fearon, Ian M.; Nides, Mitch; Eldridge, Alison; Camacho, Oscar M.; Murphy, James; Proctor, Christopher J. (International Journal of Clinical Trials, 2017)
Background: Smoking is a leading cause of numerous human disorders including lung cancer, chronic obstructive pulmonary disease, and atherosclerotic cardiovascular disease. Nicotine is primarily responsible for the addictive properties of cigarette smoking whereas other chemical constituents of the cigarette smoke are considered responsible for disease development. Electronic cigarettes (e-cigarettes) deliver a vapour containing nicotine and which is considered to contain significantly less chemical toxicants compared to cigarette smoke. This study will investigate nicotine delivery from a novel e-cigarette device and compare it to that from both a commercially-available e-cigarette and a combustible cigarette. Methods: This study will examine nicotine pharmacokinetics in subjects while either smoking a cigarette or using one of 5 different e-cigarettes for up to 5 minutes ad libitum. The study is a single-centre, randomised controlled clinical study with a crossover design. Subjects of either gender will be aged 22–55 years (minimum legal smoking age in CA plus 1 year) and a verified smoking status (assessed by exhaled breath CO and urinary cotinine levels). Subjects will be judged to be healthy by medical history, physical examination, vital signs, ECG and clinical biochemistry tests. The primary objectives are to characterize the kinetics of nicotine absorption into the blood of subjects using different e-cigarettes or smoking a cigarette; and to compare nicotine delivery from different e-cigarettes with one another and with that from a conventional cigarette. Conclusions: Data from this study will advance our scientific understanding of the pharmacokinetics of nicotine in smokers who use different types of e-cigarettes.